Detecção dos genes de virulência e identificação do perfil clonal de isolados de Staphylococcus aureus colonizantes de nasofaringe otbtidos em estudo de base populacional - Abraão, Lígia Maria [UNESP] (2013)
Recent findings show an increase on the incidence and severity of Staphylococcus aureus infection. This fact is worsened by the wide dissemination of the methicillin-resistant S. aureus (MRSA) isolates in hospitals and its recent introduction in the community settings. The nasal colonization in asymptomatic individuals remains the main factor responsible for the persistence and dissemination of S. aureus in the human population. Thereby, nasal carriage surveys are an important tool in order to estimate the total S. aureus burden and the MRSA in the community. Besides, understanding the bacterial-host relationship and the virulence factors involved is necessary in order to manage the infections that jeopardize the population’s health. The present study aims at investigating the clonal distribution of S. aureus and MRSA strains in an urban population area in Botucatu, SP, identifying both the prevalence of the virulence determinants together to the associated risk factors in samples obtained from the nasopharynx of healthy individuals from Botucatu. A total of 223 S. aureus samples isolated from nasal secretions were submitted to the antimicrobial susceptibility tests through the disk-difusion method with oxacillin and cefoxitin disks. The E-test method with oxacillin was applied in order to obtain the Minimum Inhibitory Concentration (MIC) among oxacillin disk resistant samples. Afterwards, PCR (Polimerase Chain Reaction) was carried out for the detection of the mecA gene and of the following virulence genes: enterotoxins (sea, seb and sec), toxic shock syndrome toxin (tst), exfoliative toxin A and B (eta, etb), Panton-Valentine Leukocidin (lukS-PV and lukF-PV), alphaand delta-hemolysins (hla and hld), and biofilms (icaA and icaD). The PFGE molecular typing was employed in order to determine the prevalent clusters. The univariate and multivariate linear regression was carried out so that the risk factors ...